Formulation and in-vitro characterization of curcumin loaded microsphere hydrogel for the management of vitiligo - Raj, Aman; Shrivastava, Pranjul; Prasad Tiwari, Sandip (Journal of Neonatal Surgery, 2025)
Vitiligo is a chronic skin disorder characterized by the progressive loss of melanocytes, leading to depigmented patches. Conventional treatments often face limitations such as incomplete repigmentation and adverse effects. Curcumin, a natural polyphenolic compound derived from Curcuma longa, has shown promising antioxidant, anti-inflammatory, and melanogenic activities, making it a potential therapeutic agent for vitiligo. However, its clinical application is hindered by poor solubility, stability, and bioavailability. This study aimed to develop and evaluate a novel curcumin-loaded microsphere hydrogel system for the sustained and localized delivery of curcumin to vitiliginous skin. Curcumin-loaded microspheres were prepared using the solvent evaporation technique, characterized for particle size, morphology, encapsulation efficiency, and drug loading. These microspheres were then incorporated into a Carbopol-based hydrogel, which was further evaluated for pH, viscosity, spreadability, swelling index, and in-vitro drug release behavior. The formulated microspheres exhibited uniform spherical morphology with high encapsulation efficiency, while the hydrogel demonstrated desirable physicochemical properties suitable for topical application. In-vitro drug release studies indicated a sustained release profile, following Higuchi kinetics, suggesting effective drug retention and controlled delivery. In conclusion, the curcumin-loaded microsphere hydrogel system offers a promising approach for the topical management of vitiligo, potentially enhancing therapeutic efficacy while minimizing systemic side effects.